2016
DOI: 10.1371/journal.pone.0165162
|View full text |Cite
|
Sign up to set email alerts
|

Loukoumasomes Are Distinct Subcellular Structures from Rods and Rings and Are Structurally Associated with MAP2 and the Nuclear Envelope in Retinal Cells

Abstract: “Rods and rings” (RR) and loukoumasomes are similarly shaped, subcellular macromolecular structures with as yet unknown function. RR, so named because of their shape, are formed in response to inhibition in the GTP or CTP synthetic pathways and are highly enriched in the two key enzymes of the nucleotide synthetic pathway. Loukoumasomes also occur as linear and toroidal bodies and were initially inferred to be the same as RR, largely due to their shared shape and size and the fact that it was unclear if they s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Observing by fluorescence microscope, the anti‐RR has a variety of structures, but there are two basic forms—rods 3‐10μm length and rings 2‐5μm diameter. And the formations between rods and rings are also been reported, looking like ‘sewing pin’ and ‘figure eight’ . Although the exact components of RR are still not very clear, inosine monophosphate dehydrogenase type 2 (IMPDH2) and cytidine triphosphate synthase 1 (CTPS1) are definitely the components of RR .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observing by fluorescence microscope, the anti‐RR has a variety of structures, but there are two basic forms—rods 3‐10μm length and rings 2‐5μm diameter. And the formations between rods and rings are also been reported, looking like ‘sewing pin’ and ‘figure eight’ . Although the exact components of RR are still not very clear, inosine monophosphate dehydrogenase type 2 (IMPDH2) and cytidine triphosphate synthase 1 (CTPS1) are definitely the components of RR .…”
Section: Introductionmentioning
confidence: 99%
“…And the formations between rods and rings are also been reported, looking like 'sewing pin' and 'figure eight'. 4,5 Although the exact components of RR are still not very clear, inosine monophosphate dehydrogenase type 2 (IMPDH2) and cytidine triphosphate synthase 1 (CTPS1) are definitely the components of RR. 6 It is reported that IMPDH2 can catalyse the conversion of inosine monophosphate into xanthosine monophosphate in the GTP biosynthesis pathway and CTPS1 can catalyse the conversion of uridine triphosphate into cytidine triphosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Cytoophidia are also smaller than RRs and lack ring-shaped structures ( Figure 6 ). Loukomasomes, another large cellular structure similar in appearance to RRs, have been reported ( Noble et al. , 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…Our STED analyses suggested that the ability of γ-tubulin to oligomerize and aggregate might be behind the rod formation. Linear inclusions positive for γ-tubulin and actin observed in nuclei and the perinuclear area in mature neurons were suggested to serve as a supply of the centrosomal material in non-dividing cells [56].…”
Section: γ-Tubulin Has An Intrinsic Ability To Assemble Filaments mentioning
confidence: 99%
“…It is most likely the fibrillar nature of γ-tubulin that is behind its interaction with other cytoskeletal systems: with microtubules [37], actin cytoskeleton [39] and with intermediate filaments [40,41]. Rod-like intranuclear inclusions containing γ-tubulin are present in neuronal and retinoblastoma cells [56,76], as well as in plant cells [2]. γ-Tubulin positive nuclear inclusions are closely associated with lamins in cancer cells [56].…”
Section: γ-Tubulin Interacts With Lamin and The Interaction Is Reqmentioning
confidence: 99%